Labour market integration of young refugees and asylum seekers: a look at perceived barriers and resources. Issue 2 (4th March 2021) - Udayar, Shagini; Fedrigo, Laurence; Durante, Federico; Clot-Siegrist, Eva; Masdonati, Jonas
ABSTRACT: Immigration has been increasing at a significant rate over the past decades. The labour market integration of immigrants—especially of young refugees and asylum seekers—is a major challenge for not only the host country but also the immigrants themselves. This study is based on narrative career counselling, specifically the "journey of life" narrative metaphor; it is aimed at exploring the barriers and resources that 14 refugees and asylum seekers (ages 19–25) enrolled in a state integration programme in the French-speaking part of Switzerland perceive in their quest for labour market integration. The results show that language proficiency is the main barrier and that they can rely on a host of resources to achieve sustainable labour market integration.